2012
DOI: 10.1007/s00787-012-0275-8
|View full text |Cite
|
Sign up to set email alerts
|

Trainee experiences of Child and Adolescent Psychiatry (CAP) training in Europe: 2010–2011 survey of the European Federation of Psychiatric Trainees (EFPT) CAP working group

Abstract: The objective of this study was to investigate trainee experiences of Child and Adolescent Psychiatry (CAP) training across Europe in the following domains: (A) structure and organisation of training; (B) training quality and content; and (C) working conditions and recruitment. CAP trainee representatives were contacted via email across 34 countries in Europe using the European Federation of Psychiatric Trainees (EFPT) email list to complete a survey on CAP training in 2010-2011. The European Union of Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
1
18
0
1
Order By: Relevance
“…From the perspective of the families, they often have trusted and long-standing relationships with their PCPs and prefer the lack of stigma associated with being treated by paediatricians and general practitioners [46]. The global and ongoing lack of child and adolescent psychiatrists [29,43,53,60] is another reason for primary health care utilization of mentally ill minors. Moreover, access to mental health care for adolescents is often impeded by the design of the relevant health system (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of the families, they often have trusted and long-standing relationships with their PCPs and prefer the lack of stigma associated with being treated by paediatricians and general practitioners [46]. The global and ongoing lack of child and adolescent psychiatrists [29,43,53,60] is another reason for primary health care utilization of mentally ill minors. Moreover, access to mental health care for adolescents is often impeded by the design of the relevant health system (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, all of the informants who contributed to the CACAP‐FE study were familiar with CAP training and CAMH service systems in their countries or areas, and therefore there was reasonable confidence in the accuracy of the information provided. Third, although the updated study was enhanced by new questions on the contents of CAP clinical rotations, further details, such as the modalities of treatment learned, availability of specialty clinical experiences (e.g., autism spectrum disorder, obsessive compulsive disorder), how trainees are evaluated by supervisors, and so forth, were not examined in the present study given that we assumed there would not be adequate data available in this region at the time when the present study was conducted and that extant research conducted in Europe showed a large variability of these data among countries . Fourth, we did not include information about pathways to becoming child and adolescent psychiatrists.…”
Section: Discussionmentioning
confidence: 98%
“…These numbers would represent overall underdevelopments of CAP training structures in this region compared with other regions, including Europe and the North America. One study conducted in Europe shows the existence of national training standards for CAP trainees in 27 out of 28 countries . Additionally, in the USA, the core competencies required for CAP trainees are well defined and structured by the Accreditation Council for Graduate Medical Education, establishing national training standards…”
Section: Discussionmentioning
confidence: 99%
“…Training in CAP varies widely across international contexts and there is a large disparity of standards and practice in CAP including European countries where it has been formally compared (Simmons et al, 2012). In some countries, CAP has well-established roots as a separate specialty, whereas in others, the work is carried out by general psychiatrists or pediatricians.…”
Section: Cap As a Distinct Medical Specialtymentioning
confidence: 99%
“…Of the 34 European countries for whom data was collected about child psychiatry (Simmons et al, 2012), six (Belarus, Bosnia, Ukraine, Malta, Russia, and Spain) reported that there is no official CAP training program. The remaining 28 participants, who were Austria, Belgium, Croatia, Czech Republic, Denmark, Estonia, Finland, France, Germany, Greece, Hungary, Ireland, Israel, Italy, Latvia, Lithuania, The Netherlands, Norway, Poland, Portugal, Romania, Serbia, Slovakia, Slovenia, Sweden, Switzerland, Turkey, and the United Kingdom, reported official CAP training programs.…”
Section: Cap As a Distinct Medical Specialtymentioning
confidence: 99%